Alternative biomarkers for assessing glycemic control in diabetes: fructosamine, glycated albumin, and 1,5-anhydroglucitol - Ji-Eun Lee (Korean Society of Pediatric Endocrinology, 2015)
The growing attention to alternative glycemic biomarkers including fructosamine, glycated albumin (GA), 1,5-anhydroglucitol (1,5-AG), is attributable to the limitations of the glycated hemoglobin (HbA1c) assay. It is important to recognize the conditions in which HbA1c levels may be difficult to interpret. Serum fructosamine and GA have been proposed useful tools for monitoring of short-term glycemic control. These biomarkers not only reflect well glycemic control in hematologic disorder, but also represent postprandial glucose fluctuation. Serum 1,5-AG may be useful for estimating within-day glucose variation. Use of these nontraditional tests can be more helpful in the management of diabetes as complement traditional measures. Further larger cohort studies are warranted to determine whether nontraditional biomarkers have potential utility for early diagnosis, management of diabetes, and prevention of diabetic complications.